Validation of the student version of the perceptions of inclusion questionnaire in Finland - Koskela, Teija; Kyttälä, Minna; Sinkkonen, H.-M. (Informa UK Limited, 2025)
The Perceptions of Inclusion Questionnaire (PIQ; Venetz, M., Zurbriggen, C. L. A., Eckhart, M., Schwab, S., & Hessels, M. G. P. (2015). The Perceptions of Inclusion Questionnaire (PIQ). German Version. www.piqinfo.ch) was developed to analyse student’s emotional well-being at school, social inclusion and academic self-concept. This threefold questionnaire includes versions for students, their parents and teachers. The current study aimed to validate the Finnish student version of the PIQ (PIQ-Fin) using primary school data. A total of 621 Finnish students aged 10–13 in mainstream classrooms participated in this study. The results suggest that the three-factor structure of emotional school well-being, social inclusion and academic self-concept fit the Finnish sample well across gender groups and all grade levels. However, one problematic item that loaded on all three dimensions requires further inspection in future studies. Despite this issue, the PIQ-Fin remains a valuable tool for assessing Finnish children’s social, emotional and academic inclusion in school.